(3GdUjO hGdbfUs - (3HOQ GdOjf GdJfhNjs
(3ChdgG (B:s
(3hhQO ai Pdc GMGOjK fHhjI eTghQI ,adeG GHjM Pdc UGQ GdbfGUhf jMJGdhf Ydi UjO GdHMQ ,GeG UjO GdHQ hGdHMQ aHGdTHGc hGdSfGfjQ hZjQ Pdc, hGdHQ HGdLhGQM hZjQgG s
(3BNQgG (B:s
(3aGPG HOJ ai dhfg UaQI agh GdNjaGfI hdG jdHK HYO Pdc GdG jSjQGaQZJ fSGNI gPG GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B16 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdCOHs